PERAN ORGANISASI MODEL PBB DALAM MELATIH KEMAMPUAN DIPLOMASI MAHASISWA - Puspa Dewi, Riqqah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The occurrence of various dynamics in the international world, such as global issues, requires students to increase their knowledge related to various issues and problems currently happening in the international world. Global issues is to participate in the Model United Nations organization Apart from helping to increase knowledge about global issues, this simulation of UN conference sessions can also hone and improve various other skills such as research, speaking, negotiating, and diplomacy skills. This article uses a qualitative research method that will explain the research results descriptively, following the empirical reality of the phenomenon. Data collection techniques in this study used literature study, which made books, reputable journals, websites, and other scientific articles as reading material and theoretical analysis. The results obtained from this article are that the Model UN organization can train students' diplomacy skills through a UN session conference that students attend. The students will act as delegates who will represent a country and are required to cooperate with other delegates in providing solutions to resolve these global issues.